2020
DOI: 10.1177/1528083720904926
|View full text |Cite
|
Sign up to set email alerts
|

Sound absorption properties for multi-layer of composite materials using nonwoven fabrics with kapok

Abstract: Kapok fiber with high degree of hollow and small fiber diameter has excellent sound absorption. To optimize the sound absorption characters at the low frequency, sound absorption coefficients and specific surface impedance of two-layer, three-layer, and four-layer materials as polyethylene film-reinforced kapok fiber nonwoven fabrics have been studied by using the impedance tube method in the frequency range of 100–2500 Hz. The layering sequence, the polyethylene films thickness, and the gradient thickness str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…also observed that insulation properties of composite materials increased with the increase of no. of layers and thickness [64]. Küçük and Korkmaz explained that thicker materials have comparatively lower air permeability that increases the acoustic properties of the materials [65].…”
Section: Resultsmentioning
confidence: 99%
“…also observed that insulation properties of composite materials increased with the increase of no. of layers and thickness [64]. Küçük and Korkmaz explained that thicker materials have comparatively lower air permeability that increases the acoustic properties of the materials [65].…”
Section: Resultsmentioning
confidence: 99%
“…They concluded that increasing kapok fiber content and thickness will enhance the absorption characteristics. In a further study, Liu et al [11] suggested to use multi-layer of composite materials using non-woven fabrics with kapok. They found that since kapok fiber has a high degree of hollow and small fiber diameter, it is an excellent sound absorption.…”
Section: Introductionmentioning
confidence: 99%
“…Azieyanti et al [18] prepared reinforced polypropylene composites using jute and kapok fibres as raw materials and compared jute and kapok fibre-reinforced polypropylene sound insulation effect composites; the results showed that the performance of the composite material, along with the increase in the quality percentage of jute and kapok fibre, increased the filling amount to 30% when the performance of the composite material was best. Liu [19] used polyethene film to fabricate the kapok fibre nonwoven fabric. The research on the sound-absorption coefficient and specific surface impedance of composite materials in the frequency range of 100-2500 Hz was carried out using the impedance tube method.…”
Section: Introductionmentioning
confidence: 99%